Crystal structure of RuvC resolvase in complex with Holliday junction substrate - Górecka, Karolina M. (Oxford University Press, 2013)
The key intermediate in genetic recombination is the Holliday junction (HJ), a four-way DNA structure. At the end of recombination, HJs are cleaved by specific nucleases called resolvases. In Gram-negative bacteria, this cleavage is performed by RuvC, a dimeric endonuclease that belongs to the retroviral integrase superfamily. Here, we report the first crystal structure of RuvC in complex with a synthetic HJ solved at 3.75 Å resolution. The junction in the complex is in an unfolded 2-fold symmetrical conformation, in which the four arms point toward the vertices of a tetrahedron. The two scissile phosphates are located one nucleotide from the strand exchange point, and RuvC approaches them from the minor groove side. The key protein–DNA contacts observed in the structure were verified using a thiol-based site-specific cross-linking approach. Compared with known complex structures of the phage resolvases endonuclease I and endonuclease VII, the RuvC structure exhibits striking differences in the mode of substrate binding and location of the cleavage site.